2022
DOI: 10.7759/cureus.32337
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Controlled Trial to Assess the Efficacy of a Pre-operative Virtual Operation Theatre Tour on Anxiety and Patient Satisfaction in Adults Undergoing Elective Surgery

Abstract: Background: The study objective involves the evaluation of preoperative audiovisual information on the operation theater environment as a tool to relieve anxiety in patients posted for infra umbilical elective surgery under spinal anesthesia. Perioperative anxiety is detrimental to both intraoperative hemodynamic instability and postoperative recovery.Material and methods: The design was a single-center, prospective, randomized control trial. There were 120 patients in this study within the 18-60-year-old age … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…A systematic review conducted in 2017 including 27 studies regarding the format of information and its effect on anxiety found no signi cant change by the use of either verbal information, multimedia or text or combinations of those 30 . More recent reports regarding the mode of information vary from studies assessing the informant setting (physician versus peri-anaesthesia nurse with physician as back-up for di cult situations and informed consent) 41 , the use of multimedia such as by providing virtual operating room tours 42 , using videos for the preoperative visit such as for abdominal surgery 43 or spinal anaesthesia 44,45 or providing online communication platforms 46 . (Table 7) Still, the scoring systems used to measure patient satisfaction and anxiety, the timing of the measurement of both patient satisfaction and anxiety as well as the timing of interventions such as the examples named above vary widely as depicted in Table 7 thus leaving clinicians with numerous open questions.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review conducted in 2017 including 27 studies regarding the format of information and its effect on anxiety found no signi cant change by the use of either verbal information, multimedia or text or combinations of those 30 . More recent reports regarding the mode of information vary from studies assessing the informant setting (physician versus peri-anaesthesia nurse with physician as back-up for di cult situations and informed consent) 41 , the use of multimedia such as by providing virtual operating room tours 42 , using videos for the preoperative visit such as for abdominal surgery 43 or spinal anaesthesia 44,45 or providing online communication platforms 46 . (Table 7) Still, the scoring systems used to measure patient satisfaction and anxiety, the timing of the measurement of both patient satisfaction and anxiety as well as the timing of interventions such as the examples named above vary widely as depicted in Table 7 thus leaving clinicians with numerous open questions.…”
Section: Discussionmentioning
confidence: 99%